The Growing Power of Judges in Democratic Political Systems: Causes and Manifestations - Bertrand Mathieu (İdare Hukuku ve İlimleri Dergisi)
The rise of judicial power is one of the major developments in contemporary constitutional law. This is reflected particularly by the multiplication of the courts’ function and the corresponding strengthening of their normative power. This expansion of judicial power is occurring within a favorable legal, social and political context, notably due to the prominent role that fundamental rights hold across all areas of the law, the increasing criminalization of political and social life, and the role of courts in the regulation of relationships between legal orders. Judges hold genuine normative power, as evidenced, for example, by the constructive case law of the European Court of Human Rights or the use of the principle of proportionality. Furthermore, in France, administrative judges are vested with injunctive powers. The transformation of the judiciary into a real power, or its aspiration to become one, is part of a broader trend of dilution of state power. The judiciary’s role in the building of a new non-state legal order, such as the European Union or the Council of Europe, is an illuminating demonstration of the role of the judiciary in contemporary societies.